KREDIT DI SEKTOR USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) MENJADI ALTERNATIF DITENGAH KRISIS KEUANGAN GLOBAL - H. Natsir Muhammad (AkMen JURNAL ILMIAH, 2008)
Collapse of companys share being based on housing credit at year-end 2008, making business perpetrator perforced moving and look for more other invesment type make a promise. Big scale banks have non-stoped to set eye on credit compartment in small medium micro business sector. This sector is potential value and more put up with crisis so that channeling of credit small medium bisness can become alternative in the middle of tardy the corporation sector. Credit to small medium business sector will become cake which is fought by a lot of bank because its market is which still very wide. That matter, various bank will be non-stoped to improve penetration of channeling of credit till year-end 2009, inclusive of channeling of through credit program of small effort people credit